Analisis Perbandingan Tingkat Kerusakan Jalan Pada Perkerasan Lentur Dengan Metode PCI Dan Metode SDI (Studi Kasus: Jalan As-Shofa Pekanbaru) - Aisyah Nurfakhirah Sandyna; Ayu Elfichra; Azzahra Aqilla; Kevin Novaldi; Edi Yusuf Adiman (Journal of Infrastructure and Civil Engineering, 2022)
Bina Marga has produced many methods to identify the types of road damage. IRI (International Roughness Index) and SDI (Surface Distress Index) are several methods that can be applied routinely to determine road functionality. In this study, primary data was obtained in the form of road damage dimensions such as length, width, depth of damage to obtain SDI and PCI values obtained based on the results of a survey of road conditions along 1.1 km and secondary data in the form of previous literature studies. This study aims to compare the level of road damage based on PCI and SDI methods. Based on the results of the comparison of road damage using the PCI and SDI methods, with a distance of 100 meters, the SDI values in the range of 0 – 95 are obtained. In addition, PCI values are also obtained with a range of 12% - 64%. In general, the condition of the roads on Jalan Fajar Ujung, Simpang Payung Sekaki Camat Office to Jalan Asshofa. In general, the condition of road damage is in the moderate to near bad category, so that in order to maintain the proper use of the road, road repair and maintenance is required.